Beyond observation : a history of authorship in ethnographic film (2020)
This book offers a historical account of a genre of cinema that combines two distinct practices: the craft of non-fiction film-making, and eth- nography, a particular approach to carrying out and representing social research. It is an account that straddles a period of approximately 120 years, from the middle of last decade of the nineteenth century, when the moving image camera was a primitive instrument that was troublesome and expensive to use, and which was therefore reserved to professional elites, mostly in the global North, to the middle of the second decade of the twenty-first century, by which time digital technology had brought the possibility of film-making within the range of both the technical capabilities and budgets of many millions of people the world over. During this period, there have also been major changes both in the conception of ethnography within academia and in the political constitution of the wider world. All of these factors have impacted on the development and diversification of the genre of ethnographic film, as I seek to show.